2012
DOI: 10.1186/1471-2407-12-228
|View full text |Cite
|
Sign up to set email alerts
|

Snake venom toxin from vipera lebetina turanicainduces apoptosis of colon cancer cells via upregulation of ROS- and JNK-mediated death receptor expression

Abstract: BackgroundAbundant research suggested that the cancer cells avoid destruction by the immune system through down-regulation or mutation of death receptors. Therefore, it is very important that finding the agents that increase the death receptors of cancer cells. In this study, we demonstrated that the snake venom toxin from Vipera lebetina turanica induce the apoptosis of colon cancer cells through reactive oxygen species (ROS) and c-Jun N-terminal kinases (JNK) dependent death receptor (DR4 and DR5) expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 47 publications
4
38
0
Order By: Relevance
“…Number of described snake venom proteins, including metalloproteinase, disintegrin, CLP, PLA 2 and LAAO, purified from the venom of different species have been shown to induce apoptosis interacting different pathways. 12,[17][18][19][20][21][22]40 In the present study, preliminary information showing the induction of apoptosis in K562 cells after exposure to M. lebetina obtusa venom was obtained by the observation of the morphological characteristics of apoptosis as well as activation of caspase-3 by immunohistochemistry. Caspase-3 is one of the key executioners of apoptosis.…”
Section: 3639mentioning
confidence: 99%
See 1 more Smart Citation
“…Number of described snake venom proteins, including metalloproteinase, disintegrin, CLP, PLA 2 and LAAO, purified from the venom of different species have been shown to induce apoptosis interacting different pathways. 12,[17][18][19][20][21][22]40 In the present study, preliminary information showing the induction of apoptosis in K562 cells after exposure to M. lebetina obtusa venom was obtained by the observation of the morphological characteristics of apoptosis as well as activation of caspase-3 by immunohistochemistry. Caspase-3 is one of the key executioners of apoptosis.…”
Section: 3639mentioning
confidence: 99%
“…Furthermore, venoms or purified proteins from different subspecies of M. lebetina also induced apoptosis in other various cancers and non-cancerous cells, through different mechanisms. 18,20,21,44 Sanz et al 45 identified PLA2, LAAO, metalloproteinase, serine proteinase, natriuretic peptide, disintegrin, BPP and CRISP protein families in the venom of M. l. obtusa from Armenia by mass spectrometry-based proteomics approach. Igci and Demiralp 8 reported the similar protein content with additions of NGF, VEGF and protease inhibitor for Anatolian M. l. obtusa.…”
Section: 3639mentioning
confidence: 99%
“…The interplay between oxidative stress and inflammation has been implicated in the pathophysiology of many diseases including cardiovascular diseases, diabetes, cancer, arthritis, chronic kidney and neurological diseases. Several studies have demonstrated that the snake venom and their isolated components such as PLA 2 and metalloproteases induce apoptosis in different cell types (Valko et al 2007;Brenes et al 2010;Murakami et al 2011;Park et al 2012). Venom induced cell death is currently the subject of considerable interest for toxicologists in order to understand the molecular mechanism and to explore the possible therapeutic purposes of venom.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies have also shown the inhibition of venom induced apoptosis by using antioxidant enzymes. Our previous study has also shown the protective role of crocin against viper venom induced apoptosis of platelets (Torii et al 1997;Kumar et al 2002;Park et al 2012;Liu and Chang 2009;Santhosh et al 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation